Knowledge and practices of malaysian healthy plate (quarter quarter half program) among adult community in cybercity, Kepayan, Sabah - Nasir, Ahza Mohd (Universiti Sains Malaysia, 2024)
The Malaysian Healthy Plate, known as the Quarter Quarter Half Program, is a dietary guideline aimed at promoting balanced nutrition among Malaysians. This study investigates the knowledge and practice of this program among the adult community in Cybercity Kepayan, Sabah. Using a cross-sectional design, data were collected through surveys with a representative sample of adults. In this study, majority of the participants are female, working with the government. Most of the participants are a variety of races as in Sabah (n=157, 53,7%), a single individual (n=178, 62.8%), a degree holder in education (n=147, 51.9%) and have monthly income of RM2000-RM3999 (n=84, 29.7%). Most of the participants (n=131, 46.7%) have high level of knowledge about MHP QQHP. Most of the participants (n=209, 73.9%) have a moderate level of practices about MHP QQHP. There was no significant association between socio- demographic data and level of practice of Malaysian Healthy Plate as well as level of QOL (p > 0.05). The findings reveal that while there is a general awareness of the Quarter Quarter Half Program, practical adherence is limited due to various factors such as lack of detailed understanding and accessibility to healthy food options The study underscores the need for enhanced educational efforts and community-based initiatives to bridge the gap between knowledge and practice. These findings have significant implications for public health strategies aiming to improve dietary habits and overall health in the region.